Research status of humanistic care nursing interventions for patients with hypertension complicated with anxiety (高血压合并焦虑患者的人文关怀护理研究进展) - KANG Lijuan (亢丽娟); CUI Shujie (崔淑节); SHAO Hongxia (邵红霞) (中西医结合护理)
Humanistic care is issuing a nurse's love and affection to a human being, and this type of care is formed based on nurse’s patience, compassionate love, responsibility, professional theory knowledge and standard nursing practice. There is an overlap between people with anxiety and people who have high blood pressure, and they can contribute to and exacerbate the other. This paper summarized the research status of humanistic care nursing interventions for patients with hypertension complicated with anxiety, and provided reference for decision making of clinical nursing practice of hypertension and improvement of prognosis. (人文关怀护理是以人文本, 护理人员以高度的耐心、爱心、责任心及专业理论知识和规范的操作为患者提供优质的护理服务。高血压和焦虑之间存在一定的关联, 可以互相影响并加重病情。本研究总结高血压合并焦虑患者的人文关怀护理研究现状, 旨在为临床护理方案的制定以及改善患者预后提供参考。)